When Forests Take Over After Land Abandonment: Dissolved Organic Matter Response in Headwater Mountain Streams - Estévez, Edurne; Álvarez-Martínez, Jose M.; Dittmar, Thorsten; Barquín, José; Singer, Gabriel (Frontiers in Water, 2021)
Dissolved organic matter (DOM) represents the largest pool of organic carbon in fluvial ecosystems. The majority of DOM in rivers is of terrigenous origin – making DOM composition highly dependent on vegetation cover and soil properties. While deforestation is still a worldwide anthropogenic phenomenon, current land cover change in temperate regions is often characterized by secondary succession processes following the abandonment of agricultural activities including grazing on pasturelands. This results in (secondary) forest expansion with a consequent, time-lagged transformation of soil properties. Predicting the time scale and spatial scale (i.e., location in the catchment: riparian vs upslope areas) at which such land cover changes affect the terrestrial-aquatic carbon linkage and concomitantly alter properties of fluvial DOM as drivers of carbon cycling in freshwater ecosystems represents a new scientific challenge. In an attempt to identify potential legacy effects of land cover, i.e. reaction delays of fluvial DOM to changes in land cover, we here investigate the influence of specific current and historic (2 decade-old) land cover types on molecularly resolved fluvial DOM composition in headwater mountain streams. Our analysis is based on a scale-sensitive approach weighing in the distance of land cover (changes) to the stream and ultrahigh-resolution mass spectrometric analyses. Results identified the dominance of terrigenous DOM, with phenolic and polyphenolic sum formulae commonly associated to lignins and tannins, in all the studied streams. DOM properties mostly reflected present-day gradients of forest cover in the riparian area. In more forested catchments, DOM had on average higher molecular weight and a greater abundance of O-rich phenols and polyphenols but less aliphatics. Besides the modulation of the DOM source, our results also point to an important influence of photodegradation associated to variation in light exposition with riparian land cover in defining fluvial DOM properties. Despite expectations, we were unable to detect an effect of historic land cover on present-day DOM composition, at least at the investigated baseflow conditions, probably because of an overriding effect of current riparian vegetation.